2018
DOI: 10.1111/bjh.15084
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in developing specific therapies for haemophilia

Abstract: Haemophilia therapy has undergone very rapid evolution in the last 10 years. The major limitation of current replacement therapy is the short half-life of factors VIII and IX. These half-lives have been extended by the addition of various moieties, allowing less frequent infusion regimens. Entirely novel approaches have also entered the clinic, including a bispecific antibody that mimics factor VIII and strategies that rebalance the haemostatic mechanism by reducing antithrombin through inhibition of synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 60 publications
0
42
0
2
Order By: Relevance
“…New emerging treatments will be licensed to be placed on the market and big expectation are put on their impact on patient care and management, especially for patients with inhibitors . New treatment approaches could significantly improve the lives of patients, being more convenient and easy to use than conventional therapies, thanks to the subcutaneous route of administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New emerging treatments will be licensed to be placed on the market and big expectation are put on their impact on patient care and management, especially for patients with inhibitors . New treatment approaches could significantly improve the lives of patients, being more convenient and easy to use than conventional therapies, thanks to the subcutaneous route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, novel approaches to the treatment of patients with hemophilia and inhibitors are under study or in late‐stage pipeline and include a bispecific antibody recognizing activated Factor IX and Factor X, proteins required to activate the natural coagulation cascade, with a role partially similar to the cofactor FVIII, restoring the normal blood clotting process . This antibody emicizumab is now accessing the market .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In discussing why FA and ABR got to be selected and widely adopted in hemophilia trials, and in discussing their strength and limitations, we have unsurprisingly found the modality of treatment and the attainable goals played an important role. As advanced therapies, that is treatment moving beyond factor replacement, are expected to provide a more sustained factor activity level over time, 82,83 the relative strength and limitations of FA and ABR (as surrogate measures of long-term effect of treatment) may change. When higher levels of FA are achieved and sustained, bleeding will more likely be the consequence of a traumatic event and not a spontaneous event, and thus not as good a measure of overall bleeding risk.…”
Section: Do Advanced Therapies Require Further Changes On Use Of Oumentioning
confidence: 99%
“…Currently, third and fourth generation concentrates are in production and increasingly, the trend has been towards eliminating human or animal plasma‐derived proteins in large‐scale manufacturing to reduce theoretical extraneous contaminants. Both third and fourth generation concentrates contain no supplemented animal or human proteins in cell culture, with fourth generation concentrates derived from human cell lines rather than hamster cell lines (Ling et al , ). While rFVIII has been excellent from a safety perspective, the convenience of administration has not changed substantially since the 1970s when pdFVIII was used, with severe haemophilia patients still requiring intravenous injections on alternate days.…”
Section: Clinical Use Of Recombinant Fviiimentioning
confidence: 99%